Perbedaan Kualitas Persahabatan Mahasiswa Ditinjau dari Media Komunikasi - Nessa P. D. Suyono; Sumedi P. Nugraha (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2012)
The purpose of this research was to compare the friendship quality of university students based on face to face and mediated communication. This study involved 91 students majoring in Psychology at the Universitas Islam Indonesia (sixty five females and twenty six males). Friendship Quality Scale was used to collect the data. This instrument was developed by the researchers based on Asher and Parker (1993) friendship quality aspects. Paired Sample Test technique was used to analyze the data. The researchers used the Statistical Product and Service Solution (SPSS), Windows version 12.0. as a tool to calculate the data. Results have shown that quality of friendship based on face to face communication (mean score = 171,5165) has higher score than quality offriendship based on mediated communication (mean score = 160,0989), t = 7,055, p = 0,000 (p < 0,010).Keywords: Friendship, Friendship Quality, Communication, Communication Media